Social media at workplace: A case study of employees' productivity among administrative staff at Universiti Teknologi Mara Campus Jengka, Pahang / Sahira Qistina Suffa - Suffa, Sahira Qistina (Faculty of Business and Management, 2018)
The purpose of this paper is to study the relationship between the factors of social media and employees' productivity at Universiti Teknologi MARA Campus Jengka, Pahang. A total of 113 questionnaires were distributed to the administrative employees by using simple random sampling. The unit of analysis of this study was being the administrative employees who have working in Universiti Teknologi MARA Campus Jengka which is located in Pahang. The questionnaire will be distributed to various department, such as Department of Administration, Department of Treasurer's, Department of Academic Affairs Division, Department of Research & Industry Network, Department of Student Affairs, Department of Library, Department of Auxiliary Police and Department Facilities & ICT Management both male and female regardless their position in the workplace. Meanwhile, these studies have one major hypothesis which employees' productivity and four subsidiaries hypothesis of communication channels, knowledge sharing, intention to use and intrinsic motivation. Therefore, all of the factors are the factors of social media towards employees' productivity at Universiti Teknologi MARA Campus Jengka, Pahang because all of the factors were within the range of high and very high. Besides, it was also shown that the relationship between the factors of social media at Universiti Teknologi MARA Campus Jengka, Pahang was (r=.753) and the degree of correlation was strong and have a positive relationship with employee productivity. Thus, there was a positive relationship between intrinsic motivation and employees' productivity.